And/or/not causal graphs - a model for diagnostic reasoning - Ligęza, Antoni; Fuster Parra, Pilar (Zielona Góra: Uniwersytet Zielonogórski)
The paper addresses the issues of diagnostic reasoning based on abductive analysis of causal structures. It is based on ideas emerging from an engineering approach to diagnosis of complex systems. A diagnostic process is considered as a multistage backward search procedure supported by sequential testing and ordering strategies.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka